PERANAN TUNGKU TIGO SAJARANGAN DALAM MELESTARIKAN ADAT MINANGKABAU DI DESA PARIANGAN KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT - Putra, Alridho; Isjoni, Isjoni; Ibrahim, Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The ancient Minangkabau government system was led by Datuak / Penghulu (traditional leader), Cadiak Pandai (clever clever / scientist) and Alim Ulama (Religious Expert) or known as tungku tigo sajarangan. The purpose of this research is to find out the origin and history of the tungko tigo sajarangan, to find out why there are still people who do not understand the Minangkabau tradition, the role of the Tungko tigo sajarangan in preserving Minangkabau customs to determine the causes of the shift in Minangkabau customs, and in Pariangan Village, this research is descriptive research with a qualitative approach. The types of data used are primary and secondary data. Data collection techniques, namely interviews, observation, and documentation. Data analysis using data analysis model Miles and Huberman. Tungko tigo sajarangan is a customary manners originating from Pariangan Village. One of the reasons for the lack of understanding of Minangkabau customs is due to external cultural influences and they do not want to learn about it. Minangkabau customs from ancient times until now have been similar but different in their implementation. The role of Tungku Tigo Sajarangan in preserving the Minangkabau custom in Pariangan Village has been running according to its role. Where the tungku tigo sajarangan teaches about the Minangkabau customs. The main obstacle to the Tigo Sajarangan furnace in preserving Minangkabau customs is the nature of the community, including a materialistic nature.Key Words: Role, Tigo Sajarangan Furnace, Preserving, Custom